Glycemic control in critically 111: A review - Preeti Anand; Vikas Taneja; Krishan Chugh (Wolters Kluwer Medknow Publications, 2017)
Dysglycemia is frequently encountered in critically ill patients in the intensive care units (ICU) and is associated with increased morbidity and mortality. Glycemic control in ICU has three important aspects - hyperglycemia, hypoglyce- mia and glucose variability. All three aspects carry equal importance in the management of critically ill patients and need to be understood. In this review, we will discuss about glucose metabolism in relation to glycemic control in critically ill patients- epidemiology, pathophysiology and management of hyperglycemia, hypoglycemia and glucose variability in critically ill patients.